Avaliação das características demográficas, clínicas e tratamento de pacientes com diagnóstico de Espondiloartrites acompanhados na Fundação Santa Casa de Misericórdia do Pará e em dois Consultórios Particulares de Reumatologia em Belém do Pará - SANTOS, Fernando Henrique Vasconcelos dos (2020)
INTRODUCTION: Spondylarthritis comprises a group of diseases manifested with axial inflammatory pain, associated with asymmetric peripheral arthritis, sacroiliitis, enthesopathy, negative rheumatoid factor, extra-articular manifestations, absence of subcutaneous nodules, familial aggregation and tendency to clinical overlap between diseases group. OBJECTIVE: To describe the demographic, clinical and treatment profile of patients diagnosed with Spondylarthritis accompanied at the Fundação Santa Casa de Misericórdia do Pará and at two private Rheumatology clinics in Belém do Pará. METHODOLOGY: This is a retrospective, observational study, realized in the city of Belém. The population was composed of patients with previous diagnosis of Epa according to the modified New York and ASAS criteria between 2018 and 2019. RESULTS: Of the 42 patients (73.8%) were of the genus male, mean age of diagnosis of 38.9 years, ethnicity (50%), diagnosed with Ankylosing Spondylitis (69.1%). Psoriatic Arthritis (14.3%), Reactive Arthritis (9.5%), negative family history (83.3%), mixed clinical form (54.8), married civil status (66.7%), actively working (78.6%), with low back pain (69%) as the most frequent initial joint manifestation and uveitis (38.1%) as extra-articular manifestation. The majority of the patients used NSAIDs (95.2%), corticosteroids (81%), methotrexate (61.9%) and made use of biological medication (73.8%); 38.1% used only one biological medication and 35.7% used more than one. As for the duration of illness, the mean was 13.8 years. CONCLUSIONS: Ankylosing Spondylitis was the most frequent EpA. The profile of the patient analyzed in the study was man, mean age of diagnosis of 38.9 years, married, brown, with no family history, actively working, the main uveitis being extra-articular manifestation and lumbago the main articular manifestation, using more than 3 drugs previously, with prevalence of NSAIDs.